Diagnostic value of confocal laser endomicroscopy for gastric superficial cancerous lesions. Issue 3 (30th December 2010) - Li, Wen-Bo; Zuo, Xiu-Li; Li, Chang-Qing; Zuo, Fang; Gu, Xiao-Meng; Yu, Tao; Chu, Chuan-Lian; Zhang, Ting-Guo; Li, Yan-Qing
Abstract : Background: The identification of gastric superficial cancerous lesions based on conventional white-light endoscopy (WLE) is challenging, and histological analysis remains the 'gold standard' for the final diagnosis. Confocal laser endomicroscopy (CLE) can provide in vivo histological observation without the need for biopsy. Objective: To develop and evaluate CLE imaging criteria for gastric superficial cancerous lesions and to compare the diagnostic value of real-time integrated CLE (iCLE) and WLE alone in distinguishing gastric superficial cancerous lesions. Design: Prospective study. Setting: Qilu Hospital, Shandong University, Jinan, China. Patients: A total of 182 patients were enrolled into phase I and 1786 patients were enrolled into phase II. Interventions: CLE images were blindly evaluated after endoscopy in phase I, and real-time iCLE diagnosis during endoscopy was compared with WLE diagnosis by using histopathology as a gold standard in phase II. Main outcome measurements: The validity and reliability of the CLE diagnosis for identifying gastric superficial cancerous lesions. Results: Off-line CLE diagnosis for early gastric cancers had a high sensitivity (88.1%) and specificity (98.6%). When the two-tiered CLE classification of non-cancerous lesions and cancer/high-grade intraepithelial neoplasia (HGIN) lesions was introduced, CLE diagnosis led to a higher sensitivity (90.2%) and specificity (98.5%) (phase I). Real-time iCLE diagnosis had a higher sensitivity (88.9%), specificity (99.3%) and accuracy (98.8%) for gastric superficial cancer/HGIN lesions than WLE diagnosis (sensitivity, 72.2%; specificity, 95.1%; and accuracy, 94.1%) (p<0.05) (phase II). Limitations: This was a single-centre study. Conclusions: CLE can be used to identify gastric superficial cancer/HGIN lesions with high validity and reliability.